“Wow! It’s Cool”: How Brand Coolness Affects the Customer Psychological Well-Being Through Brand Love and Brand Engagement - Attiq, Saman; Abdul Hamid, Abu Bakar; Khokhar, Munnawar Naz; Shah, Hassan Jalil; Shahzad, Amna (Frontiers in Psychology, 2022)
In this era of competition, every marketer strives to outperform their rivals by improving their brands. Increase the brand coolness may be the best way to do it. Brand coolness refers to the consumers perceptions of brands being aseptically artistic, appealing, reliable, useable, authentic, having appealed and higher status. This study has used stimulus organism response (SOR) model in integration with brand attribution theory to conduct cross sectional study and using purposive sampling technique, surveyed young consumers of smart gadgets in Pakistan. A total of 1178 responses were received and analyzed through structural equation modelling. Results found positive impact of brand coolness (stimulus) on brand love and brand engagement (both modelled as organism). Brand experience moderated these links. Brand love and brand engagement also mediated the relationship between brand coolness and consumer wellbeing and delight (Both modelled as response). These findings suggest very important contribution to theory and practice by testing unexploited outcomes of brand coolness. Especially this study contributes to the consumer wellbeing literature, again an unexploited aspect of marketing literature. Despite uniqueness of these findings, cross sectional design of this study is a major limitation. Future research may supplement these findings with the help of longitudinal studies. Marketers and practitioners may benefit from this study by improving the coolness of their brands so that they may not only increase consumer engagement with the brand but they will also make consumers happy with their brands.